2016
DOI: 10.1073/pnas.1614529113
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Notch1 synergizes with multiple pathways in promoting castration-resistant prostate cancer

Abstract: Metastatic castration-resistant prostate cancer (CRPC) is the primary cause of prostate cancer-specific mortality. Defining new mechanisms that can predict recurrence and drive lethal CRPC is critical. Here, we demonstrate that localized high-risk prostate cancer and metastatic CRPC, but not benign prostate tissues or low/intermediate-risk prostate cancer, express high levels of nuclear Notch homolog 1, translocation-associated (Notch1) receptor intracellular domain. Chronic activation of Notch1 synergizes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 58 publications
2
36
0
1
Order By: Relevance
“…Consistent with our findings, a recent study by Stoyanova et al . shows that mouse prostate tumors driven by NICD1 in combination with activation of multiple oncogenic pathways (such as AKT, Myc and Ras) exhibit a castration‐resistant phenotype . Thus, all the experiments support the notion that activation of the Notch signaling induced by ADT enhances the resistance to ADT in PCa.…”
Section: Discussionsupporting
confidence: 62%
“…Consistent with our findings, a recent study by Stoyanova et al . shows that mouse prostate tumors driven by NICD1 in combination with activation of multiple oncogenic pathways (such as AKT, Myc and Ras) exhibit a castration‐resistant phenotype . Thus, all the experiments support the notion that activation of the Notch signaling induced by ADT enhances the resistance to ADT in PCa.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have broadly shown that perturbation of the NOTCH1 signalling pathway is linked to the pathogenesis of important lung diseases, in particular, lung cancer and lung lesions [58,59]. However, it has also been proved to play a key role in breast cancer [60,61] and prostate cancer [62]. Additionally, Notch1-IC aberrant overexpression correlates with leukaemia [63] and breast cancer [9,64].…”
Section: Discussionmentioning
confidence: 99%
“…50 Recently, one study validated that activation of Notch-1 synergized with multiple pathways in promoting castration resistant prostate cancer. 51 Therefore, identification of precise mechanisms that regulate EMT process would likely be useful for exploring novel therapeutic approaches for the treatment of human cancers. It has been reported that EMT is associated with CSCs in human cancers.…”
Section: Discussionmentioning
confidence: 99%